cat theory tweaks
[lambda.git] / advanced_topics / monads_in_category_theory.mdwn
index deb5bac..d5c0941 100644 (file)
@@ -233,7 +233,8 @@ If <code>&phi;</code> is a natural transformation from `F` to `M(1C)` and <code>
          = (((join 1C) G') -v- ((M unit) G') -v- (&phi; G'))
          = ((join (1C G')) -v- (M (unit G')) -v- &gamma;)
          = ((join G') -v- (M (unit G')) -v- &gamma;)
-         since (unit G') is a natural transformation to MG', this satisfies the definition for <=<:
+         since (unit G') is a natural transformation to MG',
+         this satisfies the definition for &lt;=&lt;:
          = (unit G') <=< &gamma;
 </pre>
 
@@ -247,17 +248,33 @@ Similarly, if <code>&rho;</code> is a natural transformation from `1C` to `MR'`,
          = (((join R') -v- (M &rho;) -v- unit) G)
          = (((join R') G) -v- ((M &rho;) G) -v- (unit G))
          = ((join (R'G)) -v- (M (&rho; G)) -v- (unit G))
-         since &gamma; = (&rho; G) is a natural transformation to MR'G, this satisfies the definition for <=<:
+         since &gamma; = (&rho; G) is a natural transformation to MR'G,
+         this satisfies the definition &lt;=&lt;:
          = &gamma; <=< (unit G)
 </pre>
 
 where as we said <code>&gamma;</code> is a natural transformation from `G` to some `MR'G`.
 
+Summarizing then, the monad laws can be expressed as:
+
+<pre>
+       For all &rho;, &gamma;, &phi; in T for which &rho; <=< &gamma; and &gamma; <=< &phi; are defined:
+
+           (i) &gamma; <=< &phi; etc are also in T
+
+          (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
+
+       (iii.1) (unit G') <=< &gamma;  =  &gamma;
+               when &gamma; is a natural transformation from some FG' to MG'
+
+       (iii.2)                     &gamma;  =  &gamma; <=< (unit G)
+               when &gamma; is a natural transformation from G to some MR'G
+</pre>
 
 
 
-The standard category-theory presentation of the monad laws
------------------------------------------------------------
+Getting to the standard category-theory presentation of the monad laws
+----------------------------------------------------------------------
 In category theory, the monad laws are usually stated in terms of `unit` and `join` instead of `unit` and `<=<`.
 
 <!--
@@ -271,22 +288,29 @@ Let's remind ourselves of some principles:
 
 *      functors "distribute over composition", that is for any morphisms `f` and `g` in `F`'s source category: <code>F(g &#8728; f) = F(g) &#8728; F(f)</code>
 
-*      if <code>&eta;</code> is a natural transformation from `F` to `G`, then for every <code>f:C1&rarr;C2</code> in `F` and `G`'s source category <b>C</b>: <code>&eta;[C2] &#8728; F(f) = G(f) &#8728; &eta;[C1]</code>.
+*      if <code>&eta;</code> is a natural transformation from `G` to `H`, then for every <code>f:C1&rarr;C2</code> in `G` and `H`'s source category <b>C</b>: <code>&eta;[C2] &#8728; G(f) = H(f) &#8728; &eta;[C1]</code>.
+
+*      <code>(&eta; F)[E] = &eta;[F(E)]</code> 
+
+*      <code>(K &eta;)[E} = K(&eta;[E])</code>
+
+*      <code>((&phi; -v- &eta;) F) = ((&phi; F) -v- (&eta; F))</code>
 
 Let's use the definitions of naturalness, and of composition of natural transformations, to establish two lemmas.
 
 
-Recall that join is a natural transformation from the (composite) functor `MM` to `M`. So for elements `C1` in <b>C</b>, `join[C1]` will be a morphism from `MM(C1)` to `M(C1)`. And for any morphism <code>f:C1&rarr;C2</code> in <b>C</b>:
+Recall that `join` is a natural transformation from the (composite) functor `MM` to `M`. So for elements `C1` in <b>C</b>, `join[C1]` will be a morphism from `MM(C1)` to `M(C1)`. And for any morphism <code>f:C1&rarr;C2</code> in <b>C</b>:
 
 <pre>
        (1) join[C2] &#8728; MM(f)  =  M(f) &#8728; join[C1]
 </pre>
 
-Next, consider the composite transformation <code>((join MG') -v- (MM &gamma;))</code>.
+Next, let <code>&gamma;</code> be a transformation from `G` to `MG'`, and
+ consider the composite transformation <code>((join MG') -v- (MM &gamma;))</code>.
 
-*      <code>&gamma;</code> is a transformation from `G` to `MG'`, and assigns elements `C1` in <b>C</b> a morphism <code>&gamma;\*: G(C1) &rarr; MG'(C1)</code>. <code>(MM &gamma;)</code> is a transformation that instead assigns `C1` the morphism <code>MM(&gamma;\*)</code>.
+*      <code>&gamma;</code> assigns elements `C1` in <b>C</b> a morphism <code>&gamma;\*:G(C1) &rarr; MG'(C1)</code>. <code>(MM &gamma;)</code> is a transformation that instead assigns `C1` the morphism <code>MM(&gamma;\*)</code>.
 
-*      `(join MG')` is a transformation from `MMMG'` to `MMG'` that assigns `C1` the morphism `join[MG'(C1)]`.
+*      `(join MG')` is a transformation from `MM(MG')` to `M(MG')` that assigns `C1` the morphism `join[MG'(C1)]`.
 
 Composing them:
 
@@ -294,17 +318,17 @@ Composing them:
        (2) ((join MG') -v- (MM &gamma;)) assigns to C1 the morphism join[MG'(C1)] &#8728; MM(&gamma;*).
 </pre>
 
-Next, consider the composite transformation <code>((M &gamma;) -v- (join G))</code>.
+Next, consider the composite transformation <code>((M &gamma;) -v- (join G))</code>:
 
 <pre>
-       (3) This assigns to C1 the morphism M(&gamma;*) &#8728; join[G(C1)].
+       (3) ((M &gamma;) -v- (join G)) assigns to C1 the morphism M(&gamma;*) &#8728; join[G(C1)].
 </pre>
 
 So for every element `C1` of <b>C</b>:
 
 <pre>
        ((join MG') -v- (MM &gamma;))[C1], by (2) is:
-       join[MG'(C1)] &#8728; MM(&gamma;*), which by (1), with f=&gamma;*: G(C1)&rarr;MG'(C1) is:
+       join[MG'(C1)] &#8728; MM(&gamma;*), which by (1), with f=&gamma;*:G(C1)&rarr;MG'(C1) is:
        M(&gamma;*) &#8728; join[G(C1)], which by 3 is:
        ((M &gamma;) -v- (join G))[C1]
 </pre>
@@ -312,33 +336,34 @@ So for every element `C1` of <b>C</b>:
 So our **(lemma 1)** is:
 
 <pre>
-       ((join MG') -v- (MM &gamma;))  =  ((M &gamma;) -v- (join G)), where &gamma; is a transformation from G to MG'.
+       ((join MG') -v- (MM &gamma;))  =  ((M &gamma;) -v- (join G)),
+       where as we said &gamma; is a natural transformation from G to MG'.
 </pre>
 
 
-Next recall that unit is a natural transformation from `1C` to `M`. So for elements `C1` in <b>C</b>, `unit[C1]` will be a morphism from `C1` to `M(C1)`. And for any morphism <code>f:a&rarr;b</code> in <b>C</b>:
+Next recall that `unit` is a natural transformation from `1C` to `M`. So for elements `C1` in <b>C</b>, `unit[C1]` will be a morphism from `C1` to `M(C1)`. And for any morphism <code>f:C1&rarr;C2</code> in <b>C</b>:
 
 <pre>
-       (4) unit[b] &#8728; f = M(f) &#8728; unit[a]
+       (4) unit[C2] &#8728; f = M(f) &#8728; unit[C1]
 </pre>
 
-Next consider the composite transformation <code>((M &gamma;) -v- (unit G))</code>:
+Next, consider the composite transformation <code>((M &gamma;) -v- (unit G))</code>:
 
 <pre>
-       (5) This assigns to C1 the morphism M(&gamma;*) &#8728; unit[G(C1)].
+       (5) ((M &gamma;) -v- (unit G)) assigns to C1 the morphism M(&gamma;*) &#8728; unit[G(C1)].
 </pre>
 
-Next consider the composite transformation <code>((unit MG') -v- &gamma;)</code>.
+Next, consider the composite transformation <code>((unit MG') -v- &gamma;)</code>:
 
 <pre>
-       (6) This assigns to C1 the morphism unit[MG'(C1)] &#8728; &gamma;*.
+       (6) ((unit MG') -v- &gamma;) assigns to C1 the morphism unit[MG'(C1)] &#8728; &gamma;*.
 </pre>
 
 So for every element C1 of <b>C</b>:
 
 <pre>
        ((M &gamma;) -v- (unit G))[C1], by (5) =
-       M(&gamma;*) &#8728; unit[G(C1)], which by (4), with f=&gamma;*: G(C1)&rarr;MG'(C1) is:
+       M(&gamma;*) &#8728; unit[G(C1)], which by (4), with f=&gamma;*:G(C1)&rarr;MG'(C1) is:
        unit[MG'(C1)] &#8728; &gamma;*, which by (6) =
        ((unit MG') -v- &gamma;)[C1]
 </pre>
@@ -346,130 +371,231 @@ So for every element C1 of <b>C</b>:
 So our **(lemma 2)** is:
 
 <pre>
-       (((M &gamma;) -v- (unit G))  =  ((unit MG') -v- &gamma;)), where &gamma; is a transformation from G to MG'.
+       (((M &gamma;) -v- (unit G))  =  ((unit MG') -v- &gamma;)),
+       where as we said &gamma; is a natural transformation from G to MG'.
 </pre>
 
 
 Finally, we substitute <code>((join G') -v- (M &gamma;) -v- &phi;)</code> for <code>&gamma; &lt;=&lt; &phi;</code> in the monad laws. For simplicity, I'll omit the "-v-".
 
 <pre>
-       for all &phi;,&gamma;,&rho; in T, where &phi; is a transformation from F to MF', &gamma; is a transformation from G to MG', R is a transformation from R to MR', and F'=G and G'=R:
+       For all &rho;, &gamma;, &phi; in T,
+       where &phi; is a transformation from F to MF',
+       &gamma; is a transformation from G to MG',
+       &rho; is a transformation from R to MR',
+       and F'=G and G'=R:
 
-       (i) &gamma; <=< &phi; etc are also in T
+            (i) &gamma; <=< &phi; etc are also in T
        ==>
-       (i') ((join G') (M &gamma;) &phi;) etc are also in T
+           (i') ((join G') (M &gamma;) &phi;) etc are also in T
+
 
 
-       (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
+           (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
        ==>
-                (&rho; <=< &gamma;) is a transformation from G to MR', so:
-                       (&rho; <=< &gamma;) <=< &phi; becomes: (join R') (M (&rho; <=< &gamma;)) &phi;
-                                                       which is: (join R') (M ((join R') (M &rho;) &gamma;)) &phi;
-                       substituting in (ii), and helping ourselves to associativity on the rhs, we get:
+                    (&rho; <=< &gamma;) is a transformation from G to MR', so
+                        (&rho; <=< &gamma;) <=< &phi; becomes: ((join R') (M (&rho; <=< &gamma;)) &phi;)
+                                                       which is: ((join R') (M ((join R') (M &rho;) &gamma;)) &phi;)
 
-            ((join R') (M ((join R') (M &rho;) &gamma;)) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
-                     ---------------------
-                       which by the distributivity of functors over composition, and helping ourselves to associativity on the lhs, yields:
-                    ------------------------
-            ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
-                                                             ---------------
-                       which by lemma 1, with &rho; a transformation from G' to MR', yields:
-                                                             -----------------
-            ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (join MR') (MM &rho;) (M &gamma;) &phi;)
+                        similarly, &rho; <=< (&gamma; <=< &phi;) is:
+                                                       ((join R') (M &rho;) ((join G') (M &gamma;) &phi;))
 
-                       which will be true for all &rho;,&gamma;,&phi; just in case:
+                        substituting these into (ii), and helping ourselves to associativity on the rhs, we get:
+                ((join R') (M ((join R') (M &rho;) &gamma;)) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
+    
+                        which by the distributivity of functors over composition, and helping ourselves to associativity on the lhs, yields:
+                ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
+  
+                        which by lemma 1, with &rho; a transformation from G' to MR', yields:
+                ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (join MR') (MM &rho;) (M &gamma;) &phi;)
 
-             ((join R') (M join R')) = ((join R') (join MR')), for any R'.
+                        which will be true for all &rho;,&gamma;,&phi; only when:
+                ((join R') (M join R')) = ((join R') (join MR')), for any R'.
 
-                       which will in turn be true just in case:
+                        which will in turn be true when:
+       (ii') (join (M join)) = (join (join M))
 
-       (ii') (join (M join)) = (join (join M))
 
 
-       (iii.1) (unit F') <=< &phi;  =  &phi;
+        (iii.1) (unit G') <=< &gamma;  =  &gamma;
+                when &gamma; is a natural transformation from some FG' to MG'
        ==>
-                       (unit F') is a transformation from F' to MF', so:
-                               (unit F') <=< &phi; becomes: (join F') (M unit F') &phi;
-                                                  which is: (join F') (M unit F') &phi;
-                               substituting in (iii.1), we get:
-                       ((join F') (M unit F') &phi;) = &phi;
+                        (unit G') is a transformation from G' to MG', so:
+                        (unit G') <=< &gamma; becomes: ((join G') (M unit G') &gamma;)
 
-                       which will be true for all &phi; just in case:
+                        substituting in (iii.1), we get:
+                        ((join G') (M unit G') &gamma;) = &gamma;
 
-                ((join F') (M unit F')) = the identity transformation, for any F'
-
-                       which will in turn be true just in case:
+                        which will be true for all &gamma; just in case:
+                ((join G') (M unit G')) = the identity transformation, for any G'
 
+                        which will in turn be true just in case:
        (iii.1') (join (M unit) = the identity transformation
 
 
-       (iii.2) &phi;  =  &phi; <=< (unit F)
+
+
+        (iii.2) &gamma;  =  &gamma; <=< (unit G)
+                when &gamma; is a natural transformation from G to some MR'G
        ==>
-                       &phi; is a transformation from F to MF', so:
-                               unit <=< &phi; becomes: (join F') (M &phi;) unit
-                               substituting in (iii.2), we get:
-                       &phi; = ((join F') (M &phi;) (unit F))
-                                                  --------------
-                               which by lemma (2), yields:
-                            ------------
-                       &phi; = ((join F') ((unit MF') &phi;)
+                        unit <=< &gamma; becomes: ((join R'G) (M &gamma;) unit)
+                       
+                        substituting in (iii.2), we get:
+                        &gamma; = ((join R'G) (M &gamma;) (unit G))
+               
+                        which by lemma 2, yields:
+                        &gamma; = ((join R'G) ((unit MR'G) &gamma;)
+
+                         which will be true for all &gamma; just in case:
+                ((join R'G) (unit MR'G)) = the identity transformation, for any R'G
+
+                        which will in turn be true just in case:
+       (iii.2') (join (unit M)) = the identity transformation
+</pre>
+
+
+Collecting the results, our monad laws turn out in this format to be:
 
-                               which will be true for all &phi; just in case:
+<pre>
+       For all &rho;, &gamma;, &phi; in T,
+       where &phi; is a transformation from F to MF',
+       &gamma; is a transformation from G to MG',
+       &rho; is a transformation from R to MR',
+       and F'=G and G'=R:
+
+           (i') ((join G') (M &gamma;) &phi;) etc also in T
 
-               ((join F') (unit MF')) = the identity transformation, for any F'
+          (ii') (join (M join)) = (join (join M))
 
-                               which will in turn be true just in case:
+       (iii.1') (join (M unit)) = the identity transformation
 
        (iii.2') (join (unit M)) = the identity transformation
 </pre>
 
 
-Collecting the results, our monad laws turn out in this format to be:
 
+Getting to the functional programming presentation of the monad laws
+--------------------------------------------------------------------
+In functional programming, `unit` is sometimes called `return` and the monad laws are usually stated in terms of `unit`/`return` and an operation called `bind` which is interdefinable with `<=<` or with `join`.
+
+The base category <b>C</b> will have types as elements, and monadic functions as its morphisms. The source and target of a morphism will be the types of its argument and its result. (As always, there can be multiple distinct morphisms from the same source to the same target.)
+
+A monad `M` will consist of a mapping from types `'t` to types `M('t)`, and a mapping from functions <code>f:C1&rarr;C2</code> to functions <code>M(f):M(C1)&rarr;M(C2)</code>. This is also known as <code>lift<sub>M</sub> f</code> for `M`, and is pronounced "function f lifted into the monad M." For example, where `M` is the list monad, `M` maps every type `'t` into the type `'t list`, and maps every function <code>f:x&rarr;y</code> into the function that maps `[x1,x2...]` to `[y1,y2,...]`.
+
+
+In functional programming, instead of working with natural transformations we work with "monadic values" and polymorphic functions "into the monad" in question.
+
+A "monadic value" is any member of a type M('t), for any type 't. For example, a list is a monadic value for the list monad. We can think of these monadic values as the result of applying some function <code>(&phi; : F('t) &rarr; M(F'('t)))</code> to an argument `a` of type `F('t)`.
+
+
+Let `'t` be a type variable, and `F` and `F'` be functors, and let `phi` be a polymorphic function that takes arguments of type `F('t)` and yields results of type `MF'('t)` in the monad `M`. An example with `M` being the list monad:
+
+<pre>
+       let phi = fun ((_:char, x y) -> [(1,x,y),(2,x,y)]
 </pre>
-       when &phi; a transformation from F to MF', &gamma; a transformation from F' to MG', &rho; a transformation from G' to MR' all in T:
 
-       (i') ((join G') (M &gamma;) &phi;) etc also in T
+Here phi is defined when `'t = 't1*'t2`, `F('t1*'t2) = char * 't1 * 't2`, and `F'('t1 * 't2) = int * 't1 * 't2`.
 
-       (ii') (join (M join)) = (join (join M))
 
-       (iii.1') (join (M unit)) = the identity transformation
+Now where `gamma` is another function into monad `M` of type <code>F'('t) &rarr; MG'('t)</code>, we define:
+
+<pre>
+       gamma =<< phi a  =def. ((join G') -v- (M gamma)) (phi a)
+
+                        = ((join G') -v- (M gamma) -v- phi) a
+                                        = (gamma <=< phi) a
+</pre>
+
+Hence:
 
-       (iii.2')(join (unit M)) = the identity transformation
+<pre>
+       gamma <=< phi = fun a -> (gamma =<< phi a)
 </pre>
 
+`gamma =<< phi a` is called the operation of "binding" the function gamma to the monadic value `phi a`, and is usually written as `phi a >>= gamma`.
 
+With these definitions, our monadic laws become:
 
-7. The functional programming presentation of the monad laws
-------------------------------------------------------------
-In functional programming, unit is usually called "return" and the monad laws are usually stated in terms of return and an operation called "bind" which is interdefinable with <=< or with join.
 
-Additionally, whereas in category-theory one works "monomorphically", in functional programming one usually works with "polymorphic" functions.
+<pre>
+       Where phi is a polymorphic function from type F('t) -> M F'('t)
+       and gamma is a polymorphic function from type G('t) -> M G' ('t)
+       and rho is a polymorphic function from type R('t) -> M R' ('t)
+       and F' = G and G' = R, 
+       and a ranges over values of type F('t) for some type 't,
+       and b ranges over values of type G('t):
+
+             (i) &gamma; <=< &phi; is defined,
+                         and is a natural transformation from F to MG'
+       ==>
+               (i'') fun a -> gamma =<< phi a is defined,
+                         and is a function from type F('t) -> M G' ('t)
 
-The base category <b>C</b> will have types as elements, and monadic functions as its morphisms. The source and target of a morphism will be the types of its argument and its result. (As always, there can be multiple distinct morphisms from the same source to the same target.)
 
-A monad M will consist of a mapping from types C1 to types M(C1), and a mapping from functions f:C1&rarr;C2 to functions M(f):M(C1)&rarr;M(C2). This is also known as "fmap f" or "liftM f" for M, and is called "function f lifted into the monad M." For example, where M is the list monad, M maps every type X into the type "list of Xs", and maps every function f:x&rarr;y into the function that maps [x1,x2...] to [y1,y2,...].
 
+            (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
+       ==>
+                         (fun a -> (rho <=< gamma) =<< phi a)  =  (fun a -> rho =<< (gamma <=< phi) a)
+                         (fun a -> (fun b -> rho =<< gamma b) =<< phi a)  =  (fun a -> rho =<< (gamma =<< phi a))
 
+          (ii'') (fun b -> rho =<< gamma b) =<< phi a  =  rho =<< (gamma =<< phi a)
 
 
-A natural transformation t assigns to each type C1 in <b>C</b> a morphism t[C1]: C1&rarr;M(C1) such that, for every f:C1&rarr;C2:
-       t[C2] &#8728; f = M(f) &#8728; t[C1]
 
-The composite morphisms said here to be identical are morphisms from the type C1 to the type M(C2).
+         (iii.1) (unit G') <=< &gamma;  =  &gamma;
+                 when &gamma; is a natural transformation from some FG' to MG'
 
+                         (unit G') <=< gamma  =  gamma
+                         when gamma is a function of type FQ'('t) -> M G'('t)
 
+                         fun b -> (unit G') =<< gamma b  =  gamma
 
-In functional programming, instead of working with natural transformations we work with "monadic values" and polymorphic functions "into the monad" in question.
+                         (unit G') =<< gamma b  =  gamma b
+
+                         As below, return will map arguments c of type G'('t)
+                         to the monadic value (unit G') b, of type M G'('t).
+
+       (iii.1'') return =<< gamma b  =  gamma b
+
+
+
+         (iii.2) &gamma;  =  &gamma; <=< (unit G)
+                 when &gamma; is a natural transformation from G to some MR'G
+       ==>
+                         gamma  =  gamma <=< (unit G)
+                         when gamma is a function of type G('t) -> M R' G('t)
+
+                         gamma  =  fun b -> gamma =<< ((unit G) b)
+
+                         Let return be a polymorphic function mapping arguments
+                         of any type 't to M('t). In particular, it maps arguments
+                         b of type G('t) to the monadic value (unit G) b, of
+                         type M G('t).
+
+                         gamma  =  fun b -> gamma =<< return b
+
+       (iii.2'') gamma b  =  gamma =<< return b
+</pre>
+
+Summarizing (ii''), (iii.1''), (iii.2''), these are the monadic laws as usually stated in the functional programming literature:
+
+*      `fun b -> rho =<< gamma b) =<< phi a  =  rho =<< (gamma =<< phi a)`
+
+       Usually written reversed, and with a monadic variable `u` standing in
+       for `phi a`:
+
+       `u >>= (fun b -> gamma b >>= rho)  =  (u >>= gamma) >>= rho`
 
-For an example of the latter, let &phi; be a function that takes arguments of some (schematic, polymorphic) type C1 and yields results of some (schematic, polymorphic) type M(C2). An example with M being the list monad, and C2 being the tuple type schema int * C1:
+*      `return =<< gamma b  =  gamma b`
 
-       let &phi; = fun c &rarr; [(1,c), (2,c)]
+       Usually written reversed, and with `u` standing in for `phi a`:
 
-&phi; is polymorphic: when you apply it to the int 0 you get a result of type "list of int * int": [(1,0), (2,0)]. When you apply it to the char 'e' you get a result of type "list of int * char": [(1,'e'), (2,'e')].
+       `u >>= return  =  u`
 
-However, to keep things simple, we'll work instead with functions whose type is settled. So instead of the polymorphic &phi;, we'll work with (&phi; : C1 &rarr; M(int * C1)). This only accepts arguments of type C1. For generality, I'll talk of functions with the type (&phi; : C1 &rarr; M(C1')), where we assume that C1' is a function of C1.
+*      `gamma b  =  gamma =<< return b`
 
-A "monadic value" is any member of a type M(C1), for any type C1. For example, a list is a monadic value for the list monad. We can think of these monadic values as the result of applying some function (&phi; : C1 &rarr; M(C1')) to an argument of type C1.
+       Usually written reversed:
 
+       `return b >>= gamma  =  gamma b`